2000
DOI: 10.1046/j.1365-2516.2000.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of inhibitor development in severe haemophilia A children treated with cryoprecipitate and low‐dose immune tolerance induction

Abstract: The frequency of factor VIII inhibitor development was evaluated in a hundred severe haemophilia A patients < 18 years of age (mean 10.4 +/- 5.1 years); 25 were previously untreated patients (PUPs), with a mean age of 11.2 +/- 2.9 months. All were followed up for 3 years from December 1996. Immune tolerance (IT) was induced with low-dose factor VIII (FVIII); 25-50 IU kg(-1) every other day for the 10 haemophiliacs who developed persistent inhibitors. The incidence of inhibitors for PUPs was 3/25 (12%; 95% conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
0
12
1
Order By: Relevance
“…In this study, positive factor VIII inhibitor was found in 16 patients (35%). The prevalence of factor VIII inhibitor in this study was higher than that in studies by El Alfy et al 16 and Kavakli et al 17 The difference between these studies, apparently, was caused by different methodologies that were applied. In our study, determination of the presence of inhibitor was done only once, hence we were not able to rule out the presence of transient inhibitor.…”
Section: Prevalence Of Factor VIII Inhibitorcontrasting
confidence: 81%
See 2 more Smart Citations
“…In this study, positive factor VIII inhibitor was found in 16 patients (35%). The prevalence of factor VIII inhibitor in this study was higher than that in studies by El Alfy et al 16 and Kavakli et al 17 The difference between these studies, apparently, was caused by different methodologies that were applied. In our study, determination of the presence of inhibitor was done only once, hence we were not able to rule out the presence of transient inhibitor.…”
Section: Prevalence Of Factor VIII Inhibitorcontrasting
confidence: 81%
“…El Alfy et al 16 obtained a low prevalence, 10%, of inhibitor among severe hemophilia-A patients who received cryoprecipitate. The study was a prospective study and the Bethesda assay examination was conducted every six months in order to rule out any transient inhibitor.…”
Section: Prevalence Of Factor VIII Inhibitormentioning
confidence: 99%
See 1 more Smart Citation
“…A Turkish study showed only 26% achieving success (half‐life > 6 hours). Early Egyptian study results suggested that patients with pre‐ITI inhibitor titer < 30 BU usually had a good response. The success rate in patients with pre‐ITI inhibitor titer > 40 BU was lower, at 66%.…”
Section: Discussionmentioning
confidence: 99%
“…In six of the studies [17,36,[38][39][40][41], patients were treated with a variety of FVIII preparations; in the remaining 15 studies, only one preparation was used. Nine studies [18,31,32,34,[36][37][38]42,43] were restricted to patients with severe haemophilia (FVIII:C < 2% or less), although others did report the incidence separately for patients with different grades of severity of disease (see Table 7). Almost all studies recruited predominantly infants and children.…”
Section: Studies Of the Incidence Of Inhibitor Developmentmentioning
confidence: 99%